Thrust and Flow Prediction in Gas Turbine Engine Indoor Sea-Level Test Cell Facilities - Gullia, Alessandro (Cranfield University, 2006)
The principal aim of this research was to provide a detailed understanding of the performance of gas turbine engines inside indoor sea-level test beds. In particular the evaluation of both thrust correction factors and the estimation of the mass flow entering the test cell were at the core of the research. The project has been fully sponsored by Rolls-Royce pIc. Initially, their principal objective was to assess the relevance and accuracy of CFD when applied to thrust measurement inside indoor test beds with an intended outcome of minimising the use of expensive experimental measurements. The different system interfaces and accounting systems for in-flight conditions, available in the open literature have been developed and adapted for indoor environments. This has led to the definition of three different thrust correction equations using alternative definitions of thrust correction factor. Aero-dynamic principles have been applied for the derivation of one-dimensional relationships for the calculation of each thrust correction factor using generic engine-cell performance and dimensions. A one-dimensional analytical model has been developed to represent the enginedetuner ejector pump. This is able to characterise the engine-cell system performance and is used as the main tool for providing a matching procedure capable of predicting the cell entrainment ratio. By processing experimental data relevant to different engine-cell configurations through the ejector pump analytical model, a method for achieving the entrainment ratio control inside the cell has been identified. The CFD work has been concentrated into three main activities: • A quantitative extrapolation of the thrust correction factors including, the pre-entry force, the external and the total bellmouth force, the throat stream force, the intake momentum drag and the base drag. • The representation of the engine-detuner ejector performance for a variety of engine-cell configurations. • The modelling of the generic test cell components including the inlet stack, the cascade elbow, the exhaust stack & the blast basket. The outcomes of this research have been very successful in enhancing the validity of the thrust correction equations developed .. In particular, the use of a one-dimensional approach in their estimation has been shown to be fully justified. The work has also emphasised the value of CFD in supporting the derivation of the matching procedure for predicting and controlling cell entrainment ratio. Indeed, one of the strongest outcomes of this work has been the conclusion that both the engine-cell characteristic lines computed with the one-dimensional model and those computed with CFD for different cell configurations are almost identical. In addition, the use of CFD as a tool for the quantitative evaluation of the thrust correction factors has been established. Finally, the CFD results have facilitated an enhanced understanding of the complex flow structure inside indoor test cells